1977
DOI: 10.1136/jcp.30.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and di-iodohydroxyquinoline therapy in acrodermatitis enteropathica.

Abstract: SUMMARY A 25-year-old patient with acrodermatitis enteropathica who had been treated with di-iodohydroxyquinoline for 20 years was changed to zinc sulphate therapy and studied under full metabolic balance control for zinc, calcium, magnesium, and inorganic phosphorus. The results obtained indicate that there is only a small overall deficit of body zinc stores in this disease and that the function of di-iodohydroxyquinoline is to increase the amount of zinc absorbed and retained by the body.It has been shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In our studies of one patient during commencement of zinc therapy, balance studies revealed that she retained approximately 120 mg of zinc in total which was less than 10% of her expected total body zinc (Jackson 1977). Thus it may be that the depletion of only a small specific "pool" of zinc (such as the membrane-bound zinc, as proposed by Bettger and O'Dell 1981, or the "exchangeable pool" of zinc described by Jackson et al 1984) is sufficient to produce severe zinc deficiency symptoms (see also Chap.…”
Section: Inherited Disorders Of Zinc Metabolismmentioning
confidence: 92%
“…In our studies of one patient during commencement of zinc therapy, balance studies revealed that she retained approximately 120 mg of zinc in total which was less than 10% of her expected total body zinc (Jackson 1977). Thus it may be that the depletion of only a small specific "pool" of zinc (such as the membrane-bound zinc, as proposed by Bettger and O'Dell 1981, or the "exchangeable pool" of zinc described by Jackson et al 1984) is sufficient to produce severe zinc deficiency symptoms (see also Chap.…”
Section: Inherited Disorders Of Zinc Metabolismmentioning
confidence: 92%
“…Since a considerable amount of zinc is secreted by the intestinal mucosa and pancreas it is also intriguing that there was no evidence of any increased loss of endogenous zinc in these patients. Metabolic balance studies of patients have shown net intestinal secretion of zinc in the untreated state which can be reversed by DIH or by large supplements of zinc orally (Aggett et al, 1978;Aggett et al, 1979) or by both (Jackson, 1977) to net absorption of the element. Hambidge and colleagues (1978) found a reduced concentration of zinc in a small intestinal biopsy from an untreated patient and postulated that, in Acrodermatitis enteropathica, intestinal uptake of zinc may be abnormal.…”
Section: Pathogenesismentioning
confidence: 97%
“…The preponderance of evidence suggests that this unique syndrome was not caused by CQ alone but was related to zinc deficiency and malnutrition [30], [34]. Later in the 70′s AE was recognized as a zinc deficiency disease [27] and it was understood that CQ was functioning as an ionophore for zinc [35], [36]. Thereafter, most AE patients were treated effectively with lifelong zinc supplementation but not with CQ.…”
Section: Introductionmentioning
confidence: 99%